Plant communication in a widespread goldenrod: keeping herbivores on the move. (21st November 2016) - Morrell, Kimberly; Kessler, André
Summary: Plant communication has been documented in over 35 plant species spanning 16 families to date; however, the underlying mechanisms through which it shapes plants' ecological interactions remain less clear. Using a combination of field/laboratory bioassays, headspace volatile and leaf chemical analyses in tall goldenrod ( Solidago altissima ), we tested the hypothesis that plant‐to‐plant communication affects the performance, feeding and movement behaviour of herbivores by changing plants' chemical phenotypes. We found that plant communication accelerates herbivore movement between host plants while simultaneously reducing herbivory. This suggests that plant communication can limit herbivore loads by keeping herbivores on the move between host plants. We demonstrate that volatile chemicals emitted from herbivore‐attacked plants are sufficient to explain metabolic responses in and ecological consequences for the exposed neighbour plant. Volatile profiles of beetle ( Trirhabda virgata )‐damaged and undamaged plants show substantial compositional differences, especially in sesquiterpene emission, indicating that these differences have the potential to provide neighbouring plants with specific information about herbivores in the vicinity. Despite qualitative and phenological differences in plants' metabolic responses to herbivory‐induced volatile organic compounds (VOCs) and feeding herbivores, herbivores nonetheless respond similarly to directly damaged plants and plants exposed to VOCs from damaged neighbours as if they were of equivalently poor quality. This study suggests that by enlarging the spatial scale at which induced resistance affects the distribution of plant chemical phenotypes in plant populations, VOC‐mediated plant communication alters the movement behaviour and performance of herbivores. A lay summary is available for this article. Abstract : Lay Summary